2023
DOI: 10.3390/pr11010120
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Two-Step Electrochemical Deposition Method for Sn-Pd Electrocatalyst Synthesis for a Potential Application in Direct Ethanol Fuel Cells

Abstract: Sn-Pd electrocatalysts with a constant atomic ratio of 60 at.% Sn‒40 at.% Pd suitable for potential application in direct ethanol fuel cells were synthesized using a novel two-step electrodeposition method. First, Sn was electrodeposited in various forms of dendrites, from spear-like and needle-like to individual fern-like dendrites to a network of intertwined fern-like dendrites, by varying the cathodic potential and then performing electrodeposition of Pd at a constant current density in the second step. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…22 Unlike Ni, it was shown that Sn as a sub-layer to Pd increases the activity towards EOR. [23][24][25][26] Nevertheless, electrodeposition provides the opportunity to develop innovative structure as was shown in our previous investigations. 27,28 Various structures, such as dendrites, needles, and other disperse (irregular) forms, are very desirable for electrocatalytic reactions due to their reasonably large surface area.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…22 Unlike Ni, it was shown that Sn as a sub-layer to Pd increases the activity towards EOR. [23][24][25][26] Nevertheless, electrodeposition provides the opportunity to develop innovative structure as was shown in our previous investigations. 27,28 Various structures, such as dendrites, needles, and other disperse (irregular) forms, are very desirable for electrocatalytic reactions due to their reasonably large surface area.…”
Section: Introductionmentioning
confidence: 79%
“…In our previous work, it was shown that the surface morphology of Sn, as the sub-layer in Sn-Pd electrocatalysts, strongly affects the electrocatalytic activity of Sn-Pd electrocatalysts with a constant atomic ratio of 60 at.% Sn-40 at.% Pd in EOR. 23 The role of Sn was to contribute Pd to oxidize chemisorbed species formed during the electrooxidation of ethanol by providing adsorbed OHspecies 14,15 , thereby enhancing the catalytic performance of the bimetallic catalysts. X-ray photoelectron spectroscopy (XPS) measurements showed that the presence of Sn affects the electronic state of Pd by reducing the adsorption strength of the reaction intermediates on Pd, which has a positive effect on Sn-Pd electrocatalytic activity during the EOR.…”
Section: Introductionmentioning
confidence: 99%
“…When the alloy structure is formed, Sn modifies and enhances the electronic structure of Pd by donating an electron to Pd sites and subsequently weakening the adsorption of carbonaceous species. 32 Some SnO x residuals can be retained even under highly cathodic potentials and may actively participate in the CO 2 RR. It is believed that the presence of residual surface oxide facilitates the formation of the *CO 2 ˙ − intermediate as the rate determining step, whereas in its absence, the HER becomes the dominant cathodic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes doped with Co and N showed high catalytic efficiency attributed to the high specific surface area and the synergistic effect of Co and N co‐doping [8] . Many transition metals such as Co, Ti, Sn, Fe, Ga, Ni have been used for catalysis in alkaline medium [9–12] . TiO 2 @TiOF 2 heterojunction showed high electrical conductivity and stable cyclic stability of up to 10 000 cycles at high current density in sodium‐ion batteries [13] …”
Section: Introductionmentioning
confidence: 99%